2020
DOI: 10.1530/joe-19-0477
|View full text |Cite
|
Sign up to set email alerts
|

Absence of GIP secretion alleviates age-related obesity and insulin resistance

Abstract: Glucose-dependent insulinotropic polypeptide (GIP) is an incretin secreted from enteroendocine K cells after nutrient ingestion. Fat strongly induces GIP secretion, and GIP hypersecretion is involved in high-fat diet-induced obesity and insulin resistance. Aging also induces GIP hypersecretion, but its effect on body weight gain and insulin sensitivity remains unclear. In the present study, we investigated the effect of GIP on age-related body weight gain and insulin resistance using GIP-knockout homozygous (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…By contrast, the fact that we did not see any difference between Mgll −/− and WT mice in GLP-1 release, the first and most important effect of activation of GPR119 [67], suggests that this latter receptor is instead unlikely to be involved in any of the phenotypic differences observed here between the two genotypes. On the other hand, plasma GIP levels, another response associated with GPR119 activation, were not elevated in Mgll −/− mice following a HFD, as they were in WT mice, in agreement with previous findings of a negative role of this peptide in obesity and/or insulin resistance [68]. In fact, the plasma levels of endocrine mediators were found here to strongly correlate with the relative abundance of some gut bacterial families in a manner (positively or negatively) that was generally in agreement with the reciprocal proposed protective or exacerbating roles of these peptides in obesity and diabetes and with the aforementioned proposed metabolic function of the microbial families therewith correlated.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, the fact that we did not see any difference between Mgll −/− and WT mice in GLP-1 release, the first and most important effect of activation of GPR119 [67], suggests that this latter receptor is instead unlikely to be involved in any of the phenotypic differences observed here between the two genotypes. On the other hand, plasma GIP levels, another response associated with GPR119 activation, were not elevated in Mgll −/− mice following a HFD, as they were in WT mice, in agreement with previous findings of a negative role of this peptide in obesity and/or insulin resistance [68]. In fact, the plasma levels of endocrine mediators were found here to strongly correlate with the relative abundance of some gut bacterial families in a manner (positively or negatively) that was generally in agreement with the reciprocal proposed protective or exacerbating roles of these peptides in obesity and diabetes and with the aforementioned proposed metabolic function of the microbial families therewith correlated.…”
Section: Discussionsupporting
confidence: 92%
“…Despite early studies recognizing the therapeutic potential of GIP to promote storage of dietary triglyceride in WAT [31], data collected from genetic knock-out studies (Gip or Gipr) suggested that in the absence of a functional GIP axis, mice are protected from diet-induced obesity [14,32]. This inspired the hypothesis that GIP is an obesogenic factor, and the suggestion that inhibiting GIP activity is a viable approach for treating obesity and T2D [15].…”
Section: Gip Does Not Promote a Positive Energy Balancementioning
confidence: 99%
“…Another study demonstrated improved insulin resistance in GIP-knockout mice. 35 It is possible that the altered gastrointestinal tract improves insulin resistance via changes in the release of gastrointestinal hormones such as GLP-1 and GIP. In summary, improved insulin resistance after PD might be explained by changes in the gastrointestinal tract and hormonal secretion.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%